Ocean Literacy and Metabolic Rift Theory for Addressing the Effects of the Marine Ecological Crisis - Ribeiro Mendes Nicola, Luca; Pereira Silva, Edson; Edith Pazoto, Carmen; Duarte, Michelle (International Journal of Environmental Resilience Research and Science, 2024)
Abstract: Natural resources are used by society to produce goods and this proceeding mediated by human work which transforms nature. This process is called social metabolism and is expressed differently throughout history. In the capitalist mode of production, the exchange value subsumes use value and nature is modified on a scale beyond its reproduction capacity, establishing a metabolic rift that expands to different environments, including the marine. Ocean Literacy (OL) – understanding the human influence on the oceans and the influence of the oceans on human society – aims to contribute to overcoming the ecological crisis in the ocean, however, it is focused on a logic that ranges from the Enlightenment to post-modern perspectives. In the present work, it is proposed that OL incorporates the theory of metabolic rift in order to be able to organize society to face the challenges related to oceanic issues such as acidification, extinction of biodiversity, overfishing, etc. Finally, a case study of the “Onda Cultural’” (Cultural Wave) educational initiative of the “Laboratório de Genética Marinha e Evolução” (Marine Genetics and Evolution Laboratory) at Universidade Federal Fluminense (Rio de Janeiro, Brazil) is presented in its attempt to incorporate this theory into its OL practices and activities in public schools. Key Words: Oceanic crisis. Metabolic rift. Social metabolism. Estate schools.